Contrast‐Induced Encephalopathy After Neurointerventional Procedures: A Series of Three Cases - Wang, Kaiying; Goh, Rudy; El-Masri, Shaddy; Bacchi, Stephen; Patel, Sandy; Jannes, Jim; Kleinig, Timothy (Case reports in neurological medicine, 2025)
Introduction: Contrast‐induced encephalopathy (CIE) is a rare complication that may occur following contrast administration during endovascular interventions. The phenomenon is well‐described following coronary angiography but reports following endovascular neurointerventional procedures are sparse. This study aims to describe the clinical presentation, treatment and outcome of CIE in a tertiary metropolitan hospital in South Australia. Methods: This study describes a case series of 3 patients diagnosed with CIE following cerebral angiography within a 1‐year period in a tertiary hospital. Results: All patients developed slowly progressive (and/or new) focal or global neurological deficits 2–7 h postprocedure and exhibited characteristic neuroimaging findings. Two of three patients made an excellent recovery with supportive care, improving after 48–72 h, although one died due to the severity of her associated stroke. Conclusion: CIE should be suspected in patients presenting with acute neurological deterioration following cerebral angiography. Supportive care may lead to full recovery. Multicentre prospective cohort studies are required to better define associations, diagnostic criteria and interventions to prevent and/or treat this condition.